Combined thrombus fragmentation and catheter-directed thrombolysis in the treatment of pulmonary thromboembolism in high- and moderate-risk patients - V. Dimitrova; B. Vodenicharova; D. Dimitrov; P. Krastev (Българска кардиология)
Introduction: In recent years with the increase in the incidence of pulmonary embolism (PE) worldwide and the rapid development of new devices in interventional cardiology, there has been a tendency to expand the indications for the endovascular treatment of acute PE. Systemic thrombolysis significantly reduces mortality in patients without contraindications for the procedure but at the cost of an increased risk of bleeding. High mortality with a conservative approach in patients with high-risk PE and contraindications for fibrinolysis, as well as moderate-risk patients with a lack of clinical response to optimal anticoagulant therapy, requires a more selective treatment approach to ensure an inevitable positive hemodynamic response. Catheter-based therapy (CBT), including mechanical thrombus fragmentation and selective thrombolysis, is a combined approach with potentially increased efficacy and safety over systemic thrombolysis. In the published literature there is a lack of sufficient data on the application of this therapeutic strategy as a first-line treatment for PE. Large, randomized trials are needed to confirm the value of CBT in these patient groups and to establish precise criteria and recommendations for the initial and follow-up monitoring during treatment. Aim: To evaluate the safety and efficacy of CBT in high- and moderate-risk patients with acute PE as an initial treatment strategy at one-year follow-up. Material and methods: For the period of May 2021- 2024, a total of 35 patients with acute PE were treated in our clinic. In this retrospective study, 23 patients were included, in which a decision was made to conduct CBT as a primary strategy, (in one case there is not a long enough follow-up at this stage). The remaining 8 patients were treated conservatively with low-molecular-weight heprain (LMWH), and the systemic thrombolysis in three of patients was administered. Demographic indicators, history of deep venous thrombosis (DVT), hemodynamic status on admission, non-invasive and invasive parameters of right ventricular burden, contraindications for fibrinolysis, fatal and non-fatal post-procedural complications were recorded. The clinical follow-up is in-hospital conditions, at 6 and 12 months in terms of mortality, manifestations of heart failure, bleeding and hospitalization for PE relapse. All patients in the study group underwent right heart catheterization according to a standardized protocol. CBT includes defragmentation of the thrombi using a Pigtail catheter and selective fibrinolysis with recombinant tissue plasminogen activator /r-TPA, alteplase/ with a dosage of 0.3 mg/kg. Results: The PESI score, which evaluates 30-day mortality in patients with acute pulmonary thromboembolism based on 11 clinical criteria, was used for risk assessment The studied cohort included patients with very high and moderately high risk and an estimated PESI score in the III-V range. CBT was technically successful in 100% (n = 23) of patients. The overall clinical success of the procedure, defined as haemodynamic stability, reversal of hypoxia, reduction of respiratory rate and improvement of peripheral perfusion was achieved in 90.4% of patients. During the hospital stay, 2 deaths were registered (8.69%), the fatal outcome being due to treatment-refractory cardiogenic shock in the first case (the patient died 24 hours after admission) (4.35%) and haemorrhagic stroke in the second (4.35%). In the remaining patients, not a single haemorrhagic incident as well as serious periprocedural complications, were detected. The comparative analysis between echocardiography and invasively assessed pulmonary artery pressure (PAP) before and after the CBT shows that the decrease in the mean PAP (m-PAP) after the treatment is statistically significant - on average 10 mm Hg, which suggests a positive effect of the treatment. During the 6-month follow-up, two more deceased patients were registered – an 81-year-old woman with previous melena before treatment for PE, and with a new episode and a large drop in haemoglobin, sent for treatment to a gastroenterology department, and a second patient with an unclear cause of death - probable sudden cardiac death (SCD). (Mortality at 6 months is 8.6%). Up to 12 months, no other adverse cardiovascular events were observed in the remaining patients. Conclusion: Our experience in endovascular therapy of acute PE showed that the methodology is both therapeutically and prognostically effective, but also low-risk for the patient. A large, randomized trial is needed before the technique can be recommended as a first-line treatment.